"It's all set in the stars": adapting and staging Lee Smith's "Intensive Care"*. Issue 1 (2nd January 2016) - Allison, John M.
ABSTRACT: This essay describes the analysis, adaptation, and staging processes associated with a production of Lee Smith's short story, "Intensive Care." Smith's story, animated by a subtextual tension between religion and science, is distinctive in that she renders them as complements rather in opposition to one another, as is traditional in Southern fiction. The production utilized Salvador Dalí's painting, Corpus Hypercubus, which similarly combines the religious theme of salvation with mathematical and scientific ideas to demonstrate their consubstantiality, as a visual intertext for staging Smith's narrative. The essay details how the synergies between these two texts inspired both the voice and the visual elements of the production.